Rapid, convenient and efficient kit-independent detection of SARS-CoV-2 RNA: short communication - Michel, Detlef; Danzer, Karin M.; Groß, Rüdiger; Conzelmann, Carina; Müller, Janis A.; Freischmidt, Axel; Weishaupt, Jochen H.; Heller, Sandra; Münch, Jan; Michel, Manuela; Stamminger, Thomas; Kleger, Alexander; et al. (Journal of virological methods, 2020)
Pandemic SARS-CoV-2 infection has rapidly developed into a socioeconomic and humanitarian catastrophe. Basic principles to prevent SARS-CoV-2 transmission are social distancing, face masks, contact tracing and early detection of SARS-CoV-2. To meet these requirements, virtually unlimited test capacities delivering results in a rapid and reliable manner are a prerequisite. Here, we provide and validate such a rapid, convenient and efficient kit-independent detection of SARS-CoV-2 RNA, termed COVID-quick-DET. This straightforward method operates with simple proteinase K treatment and repetitive heating steps with a sensitivity of 94.6% in head-to-head comparisons with kit-based isolation methods. This result is supported by data obtained from serially diluted SARS-CoV-2 virus stocks. Given its cost- and time-effective operation, COVID-quick-DET might be best suited for countries with general shortage or temporary acute scarcity of resources and equipment.
Gesehen am 07.04.2021